L’artista Mario Merz e la sua installazione Fibonacci 1-55 a Turku - Lorella Scacco (Italian kielen ja kulttuurin seura ry - University of Turku, 2022)
The essay presents the lifework of the Italian artist Mario Merz (1925-2003) and its installation Fibonacci 1-55 within the framework of the project Environmental art works in Turku.